THE ROLE OF MANAGEMENT: A COMFORTABLE WORK ENVIRONMENT MOTIVATES AND IMPROVES THE SELF-EFFICACY OF INDONESIAN VILLAGE EQUIPMENT - Suherdi, Suherdi; Ahmad, Ahmad (Faculty of Economics and Business, Universitas Negeri Jakarta, 2023)
This study aims to determine the effect of the work environment and motivation on the performance of the village apparatus in Lebak Regency. This study has a total sample of 98 respondents. This research method uses research methods with a quantitative approach, survey methods, and model analysis techniques using the SPSS version 24 application. Data collection techniques include distributing questionnaires to respondents. The analysis technique used in this study is multiple linear regression, correlation coefficient analysis, and the coefficient of determination (R2). Based on the results of multiple regression analysis, with the results of the T test showing a t count value of 2.847 > t table 1.988, this means that H0 is rejected and Ha is accepted, which means that the work environment has a significant effect on the performance of village officials. Furthermore, the results of research on work motivation affect the performance of village apparatus, as evidenced by the results of the T test, which show a t count of 3.429 > t table 1.988. This means that H0 is rejected and Ha is accepted, which means that work motivation has a significant effect on the performance of the village apparatus.